2020
DOI: 10.1016/j.psj.2020.09.075
|View full text |Cite
|
Sign up to set email alerts
|

Yeast cell wall product enhanced intestinal IgA response and changed cecum microflora species after oral vaccination in chickens

Abstract: The study was designed to explore the effect of a commercial yeast cell wall product ( YP ) on chicken intestinal IgA response and cecum microbiome after oral vaccination. Chickens were fed with YP during the experiments and orally immunized with live Newcastle disease virus ( NDV ) vaccine at 2 wk of age. Then, the animals were sacrificed, and samples were collected to measure the indicators of hemagglutination inhibition ( HI ), IgA respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 41 publications
3
13
0
Order By: Relevance
“…This might be one of the reasons why SC upregulated the RA of Ruminococcaceae. This was also consistent with the finding in other studies that yeast cell wall increased the RA of Ruminococcaceae in the intestine of broilers ( Bi et al, 2020 ). The main metabolites of Ruminococcaceae and Bacteroidetes ( Harrison et al, 2018 ; Wang C et al, 2021 ) in the intestine are Short-chain fatty acids, which help to promote the growth of intestinal epithelial cells and elevate the expression of tight junction proteins ( Miao et al, 2016 ; Del et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…This might be one of the reasons why SC upregulated the RA of Ruminococcaceae. This was also consistent with the finding in other studies that yeast cell wall increased the RA of Ruminococcaceae in the intestine of broilers ( Bi et al, 2020 ). The main metabolites of Ruminococcaceae and Bacteroidetes ( Harrison et al, 2018 ; Wang C et al, 2021 ) in the intestine are Short-chain fatty acids, which help to promote the growth of intestinal epithelial cells and elevate the expression of tight junction proteins ( Miao et al, 2016 ; Del et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Avian beta-defensins (AvBDs), also known as gallinacins, are small cationic peptides having three cysteine disul de bonds between their cysteine residues and play essential roles in the innate immune system [21]. The decreased expression of cathelicidins and betadefensin might be explained by the feedback regulation, in which the population of Bacteroides and Parabacteroides were reduced by yeast cell wall polysaccharide [5]. Similar results were found in other studies.…”
Section: Gene Ontology Classi Cation and Kegg Enrichment Analysissupporting
confidence: 73%
“…Immunomodulatory effect of polysaccharides from yeast cell wall have been demonstrated effective to change immune response and altered gut microbiota composition in chickens [9][10]. In our previous study, a yeast cell wall product contained β-glucan and MOS was found effectively to enhance intestinal IgA response to NDV vaccination and modulated the cecum microbiota by oral route [5]. However, only a few reports analyzed the mRNA expression of spleen after oral administration of yeast polysaccharides.…”
Section: Gene Ontology Classi Cation and Kegg Enrichment Analysismentioning
confidence: 98%
See 1 more Smart Citation
“…Besides, yeast additives are probably supportive of immune hemostasis though medicating the balance between pro- and anti-inflammatory activities. Recent studies have found that yeast cell wall addition to feed improved serum immune response as well as intestinal integrity and immune function of animals [ 8 , 12 ]. Moreover, fractions or extracts of yeast cell wall including β-glucan and mannan-oligosaccharide (MOS) could improve intestinal barrier, anti-inflammatory and immune functions as well as regulate the microflora in the hindgut in different animals [ 13 15 ].…”
Section: Introductionmentioning
confidence: 99%